The Influence of Profitability and Liquidity on Company Value with Capital Structure as Moderating Variables - Agus Ismaya Hasanudin; Risma Nindya Primawresti; Tri Lestari (Syntax Corporation Indonesia, 2022)
This study aims to examine the effect of profitability and liquidity on company value with capital structure as a moderating variable. Company value is essential to know because it reflects growth and performance. The object of this research is pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2015-2019. because the 2015-2035 National Industrial Development Master Plan states the pharmaceutical and pharmaceutical ingredients industry is one of the mainstay manufacturing sectors that get development priority because it plays a significant role as the main driver of the national economy. This quantitative research is included in associative research to obtain information about the influence or relationship between two or more variables. The results of study shows that one company that has just been listed on the IDX from 2018 so that it becomes a deduction in the sample used.